2021
DOI: 10.3390/cancers13143592
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Body Mass Index with Oncologic Outcomes in Colorectal Cancer Patients: A Large Population-Based Study

Abstract: It has been acknowledged that excess body weight increases the risk of colorectal cancer (CRC); however, there is little evidence on the impact of body mass index (BMI) on CRC patients’ long-term oncologic results in Asian populations. We studied the influence of BMI on overall survival (OS), disease-free survival (DFS), and CRC-specific survival rates in CRC patients from the administrative claims datasets of Taiwan using the Kaplan–Meier survival curves and the log-rank test to estimate the statistical diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 64 publications
(85 reference statements)
1
16
0
Order By: Relevance
“…There were many factors that could affect the prognosis of CRC patients including tumor stage, BMI, T2DM, age and complications [ 3 , 21 24 ]. In this study, tumor stage and complications were independent predictors of CRC patients which was similar with previous studies [ 3 , 21 , 22 ]. In addition, younger aged patients were associated with better prognosis than older aged patients, which meant that after radical CRC surgery, age was an important factor affecting the prognosis.…”
Section: Discussionsupporting
confidence: 92%
“…There were many factors that could affect the prognosis of CRC patients including tumor stage, BMI, T2DM, age and complications [ 3 , 21 24 ]. In this study, tumor stage and complications were independent predictors of CRC patients which was similar with previous studies [ 3 , 21 , 22 ]. In addition, younger aged patients were associated with better prognosis than older aged patients, which meant that after radical CRC surgery, age was an important factor affecting the prognosis.…”
Section: Discussionsupporting
confidence: 92%
“…Some of the conflicting results from previous reports may be due to the different cancer types studied. For example, underweight patients (BMI < 18.50 kg/m 2 ) had higher mortality (HR 1.61, 95% CI 1.53-1.70, p < 0.0001) compared with patients with normal weight (BMI 18.50-24.99 kg/m 2 ) in colorectal cancer (18,19). However, Troeschel et al suggested that obesity at diagnosis (HR 1.23, 95% CI 1.11-1.35) and weight gain (HR 1.27, 95% CI 1.12-1.45) after a prostate cancer diagnosis may be associated with higher all-cause mortality (20).…”
Section: Discussionmentioning
confidence: 99%
“…Shahjehan F et al [ 29 ] reported that higher BMI had better OS in stage III and IV CRC patients, and another study reported that higher BMI increased the recurrence rate of stage III CRC patients [ 30 ]. The possible reason in this study was that higher BMI patients might have more muscle and fat mass, allowing them to cope with the metabolic demands of tumor progression and treatment [ 31 , 32 ]. Other studies reported lower BMI was associated with cancer-related cachexia and underlying biology in late stage disease patients, which might cause worse prognosis in lower BMI CRC patients [ 29 ].…”
Section: Discussionmentioning
confidence: 99%